Analisis laboratorium Anak Glomerulus Nefrotik Akut Paska Streptokokus di Bangsal Anak Prof.DR. R.D. Kandou Hospital - Sanusi, Holly; Umboh, Adrian; Umboh, Valetine (JKK (Jurnal Kedokteran Klinik), 2019)
ABSTRACTBackground: Acute post-streptococcal acute glomerulonephritis (GNAPS) is the most common type of glomerulonephritis in childhood. Acute glomerulonephritis (GNA) is characterized by acute onset of edema, hematuria, and hypertension, and is usually associated with oliguria and azotemia. Method: This research is a retrospective study by taking data from the medical records of children's ward Prof. Dr. RD Kandou Manado with a diagnosis of Acute Glomerulonephritis after Streptococcus with an interval of 5 years. By looking at laboratory values. Results: From the results of a complete blood test, there were 40 children (78%) with Hb levels above normal, 36 children (70%) leukocytes increased, 37 children (72%) LEDs above normal, 41 children (80%) ASTO > 200 IU, 6 children (11%) CRP increased, 27 children (52%) C3 decreased, 32 children (62%) creatinine urea increased. Potassium is below normal for 9 children (19%), Potassium is more than normal for 4 children (9.8%), serum sodium is below normal for 18 children (37%). Microscopic erythocytes are positive in 100% of children, macroscopic 42% of children. Conclusion: Microscopic haematuria is a sign found in all GNA sufferers, followed by increased ASTO, increased LEDs, increased leukocytes, and increased creatinine urea.Keyword : GNAPS, GNA, Laboratory Analysis,Post Streptococal Infection ABSTRAKLatar belakang: Glomerulonefritis akut pasca streptokokus (GNAPS) adalah jenis glomerulonefritis yang paling umum  pada masa kanak-kanak. Glomerulonefritis akut (GNA) ditandai oleh onset akut edema, hematuria, dan hipertensi, dan biasanya berhubungan dengan oliguria dan azotemia. Metode: Penilitian ini merupakan studi retrospektif dengan mengambil data dari rekam medis bangsal anak RSUP Prof dr. RD Kandou Manado dengan diagnosa Glomerulonephritis Akut Paska Streptococcus dengan selang waktu 5 tahun. Dengan melihat nilai laboratorium. Hasil: dari hasil pemeriksaan darah lengkap didapatkan, terdapat 40 anak (78%)  dengan kadar Hb di atas normal, 36 anak (70%) leukosit meningkat,  37 anak (72%) LED di atas normal, 41 anak (80%) ASTO > 200IU , 6 anak (11%) CRP meningkat, 27 anak (52%) C3 menurun, 32 anak (62%) ureum kreatinin meningkat. Kalium di bawah normal 9 anak (19%), Kalium lebih dari normal  4 anak (9,8%), natrium serum dibawah normal 18 anak (37%). Eritosit mikroskopik positif pada 100% anak, makroskopik 42% anak. Kesimpulan: Hematuria mikroskopik merupakan tanda yang ditemukan pada semua penderita GNA, diikuti oleh ASTO meningkat, LED meningkat, leukosit meningkat, dan ureum kreatinin meningkat.Kata kunci : GNAPS, GNA, Analisis Laboratorium,Post infeksi Streptococus